Breast Arterial Calcification: a Novel Cardiovascular Risk Enhancer Among Postmenopausal Women. (15th March 2022) - Iribarren, Carlos; Chandra, Malini; Lee, Catherine; Sanchez, Gabriela; Sam, Danny L.; Azamian, Farima Faith; Cho, Hyo-Min; Ding, Huanjun; Wong, Nathan D.; Molloi, Sabee
Abstract : Background: Breast arterial calcification (BAC), a common incidental finding in mammography, has been shown to be associated with angiographic coronary artery disease and cardiovascular disease (CVD) outcomes. We aimed to (1) examine the association of BAC presence and quantity with hard atherosclerotic CVD (ASCVD) and global CVD; (2) ascertain model calibration, discrimination and reclassification of ASCVD risk; (3) assess the joint effect of BAC presence and 10-year pooled cohorts equations risk on ASCVD. Methods: A cohort study of 5059 women aged 60-79 years recruited after attending mammography screening between October 2012 and February 2015 was conducted in a large health plan in Northern California, United States. BAC status (presence versus absence) and quantity (calcium mass mg) was determined using digital mammograms. Prespecified end points were incident hard ASCVD and a composite of global CVD. Results: Twenty-six percent of women had BAC >0 mg. After a mean (SD) follow-up of 6.5 (1.6) years, we ascertained 155 (3.0%) ASCVD events and 427 (8.4%) global CVD events. In Cox regression adjusted for traditional CVD risk factors, BAC presence was associated with a 1.51 (95% CI, 1.08–2.11; P =0.02) increased hazard of ASCVD and a 1.23 (95% CI, 1.002–1.52; P =0.04) increased hazard of global CVD. While there was no evidence of dose-response association with ASCVD, a threshold effect was found for global CVD at very high BAC burden (95th percentile when BAC present). BAC status provided additional risk stratification of the pooled cohorts equations risk. We noted improvements in model calibration and reclassification of ASCVD: the overall net reclassification improvement was 0.12 (95% CI, 0.03–0.14; P =0.01) and the bias-corrected clinical-net reclassification improvement was 0.11 (95% CI, 0.01–0.22; P =0.04) after adding BAC status. Conclusions: Our results indicate that BAC has potential utility for primary CVD prevention and, therefore, support the notion that BAC ought to be considered a risk-enhancing factor for ASCVD among postmenopausal women.